Implementation of Communication Management in the Learning Process in the Digitalization Era of Class X Science Students of SMK Jambi Medan - Jenni Tarigan; Yona Gulo; Fransiskus Gultom; Losten Tamba (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this paper is to improve the quality and effectiveness of message exchanges that occur in various communication contexts within the learning process. This research was conducted at SMK Jambi Medan with a sample of 39 class X students. Communication management is the process of managing communication resources that are frequently used in everyday life, including in the surrounding environment. The communication context referred to here means the individual, interpersonal, organizational, governmental, and social levels of communication. The positive impact of digital era learning media as an efficiency of communication management technological advances, providing many creative and challenging games that are apparently popular with students. The presence of digital technology does provide many benefits and can streamline communication management because work can be done easily and information becomes faster to access via the internet. However, behind it all, there are a million threats lurking, especially in generation 4.0. They are willing to spend most of their time with gadgets rather than playing in their environment. It is truly a heartbreaking reality, gadgets have become a new life for them. The negative impacts and side effects of using digital technology can include decreased academic achievement due to excessive use, limiting physical activity needed for children's growth and development, hampered development of children's social and language skills due to being introduced to gadgets early (especially at the age of under 2 years), brain development is not optimal due to unbalanced developmental stimulation, eye health problems (screen time should be limited to a maximum of 2 hours per day), concentration problems (intermittently looking at and checking gadgets), sleep problems, the amount of sleep time, and poor quality of sleep (due to the content of the viewing), no privacy, allowing personal data to be taken, child predators, cyber bullying, and others, problems with pornography, violence, or the instillation of negative values